Pembuatan program aplikasi untuk menentukan modus pandu gelombang raised-strip dari devais fotonik (Creation of a program to determine the waveguide mode lifted from the photonic device) - Genov Zulmartin; - Hidayati; Pakhrur Razi (PILLAR OF PHYSICS, 2015)
In the integrated optical system (Integrated Optics), the raised-strip waveguide is part of the photonic divices used as a medium of light propagation. Physical parameters of raised-strip waveguide mode waveguides affects that can be passed on the waveguides. Given the relative complexity of the calculations - calculations in determining the number of waveguide modes, in this research, and numerical analysis made in an application program in order to facilitate the determination of the waveguide mode. Research conducted including descriptive research using a numerical approach. Used numerical approach is the bisection method is an ideal method to find a result with the use of iterative or repetitive calculations. Furthermore, with this method using Matlab software program designed 2007.  Were run on the Windows XP operating system  based on research conducted in the form of GUI matlab program that displays the dispersion curves. Generated that variations in physical parameters such as refractive index, thickness and wavelength lebal films and give effect to the number of raised-mode strip waveguides of photonic divices. Where the greater the difference in the refractive index is given, the more the mode waveguides can be missed.